Sacred Ties to Ancestral Land: Reclaiming Indigenous Practices in Environmental Stewardship in the Cordillera - Jacoba, Rico Casta (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This study explores the importance of Indigenous beliefs and practices in the Cordillera, Philippines, highlighting the necessity of maintaining cultural and spiritual ties to the land for environmental stewardship and sustainability. The research underscores the deep connection that Cordilleran communities have with their ancestral lands, regarded as sacred and vital for cultural identity and environmental management. For instance, the muyong forest management system and water resource management rituals directly demonstrate this connection. These practices provide specific environmental benefits, including biodiversity conservation, soil fertility, and water regulation. However, these practices are increasingly threatened by modernization, industrial activities, and the decline of traditional values. The study also investigates syncretism, where Indigenous beliefs merge with Christianity, resulting in unique perspectives on environmental ethics. The methodology involves critically reviewing available written traditions, including ethnographic studies, government reports, and Indigenous oral histories from the internet and libraries around Baguio City. The data were analyzed through thematic content analysis to identify patterns and insights. Results indicate that syncretism offers a valuable framework for combining traditional and modern conservation approaches. This framework highlights integrating Indigenous spiritual practices with contemporary ecological strategies, fostering a holistic approach to conservation.